Development of Hypermedia-Based E-Modules on Reading Comprehension Material for Grade V Indonesian Language Lessons at SDN Gunung Batu 1 Bogor - Primayanti Primayanti; Zainal Abidin Arief; Widyasari (Indonesian Journal of Pedagogy and Teacher Education, 2024)
The purpose of this study was to develop and test the feasibility and effectiveness of hypermedia-based e-modules on reading comprehension material for grade V Indonesian language subjects at SDN Gunung Batu 1 Bogor.  This research uses the Research and Development (R & D) method with the Borg and Gall model which is integrated with the ADDIE model.  The research includes: (1) needs analysis and material analysis, (2) design stage, (3) initial product development, (4) initial test, (5) revision of validation test results, (6) trial use, and (7) improvement.  The results of the development of hypermedia-based e-modules on reading comprehension material for Grade V Indonesian Language lessons at SDN Gunung Batu 1 Bogor are that the product is considered feasible based on the material expert validation score of 78%, and very good and feasible based on the validation scores of media experts 90% and instructional design experts 96%.  The hypermedia-based E-Module shows its effectiveness based on the N-Gain score which gets a percentage of 75%.